A jelenlegi állapot északbácska 8 községében a 2oo9 – es népességmegtartó gazdaság fejlesztési forgatókönyvünk és foglalkoztatottsági pronózisunk tükrében (The Current State of 8 Communities in the Region North Bacska in the Light of Economic Development and Population Retention Scenario for 2009) - Sándor Somogyi; András Ricz (DETUROPE)
We had in 2010 a report to HSSV (Hungarian Scientific Society of Vojvodina) on development scenarios and employment forecast. The report and the conclusions are still valid. The development problems today are also current for Hungarian minorities who lives in Vojvodina. We recognized that number of model has limitations to treat region as complex system and to characterize the future behavior. Therefore, we used a combination of a direct questionnaires and an expert scenarioassessment method. We accepted that the most likely to achieve an economic development, which is strongly reflected in the role of the agricultural sector a certain level of small and medium-sized enterprises and remains a particular operation and stagnation. This indicates that this region of the endogenous levels of forces is not sufficient to form the engine of development. The economic development analyzes had indicated that the projections about the number of employees can be very important. The number of employees we could provide 22-year data series, which allowed the use of prognostic models. For making the forecast we used the SPSS ARIMA models. The forecasted results are based well by the R2 indicator. The employment forecasts and possible scenarios of economic development are also point in the same direction, the region's communities, but also Vojvodina and Serbia, has to take urgent measures to make further progress, to prevent the region's falling behind.